التنبؤ عن توزع الرواسب في سد 16 تشرين بالطرائق التجريبية - حماد, منذر (Latakia University Journal -Engineering Sciences Series, 2019)
Prediction of sediments distribution in reservoirs is an important issue for dam designers to determine the reservoir active storage capacity. Methods proposed to calculate sediment distribution are varied, and mainly empirical. Among all the methods currently available, only area-reduction and area-increment methods considered as the principal methods for prediction of sediment distribution. In the research, aims to study the sediments distribution in 16-Tisreen reservoir dam situated in Syria, Lattakia investigated through empirical methods of area-increment and reduction. In order to perform calculations, primary area-volume-height data of reservoir and information obtained through hydrography in years following exploitation used. Using both methods, sedimentations in reservoir calculated and compared to actual values obtained of hydrography in year 2018. Results showed that, area-reduction method by error decrease of 2 percent is preferred to area-increment method regarding 16-Tishreen reservoir dam. Afterwards, parameters used in area-reduction (C, m, n) were calibrated and this method was optimized to about 33 percent. Eventually and upon the base of calibrated parameters, sediments distribution predicted for coming 20 and 70 years, which corresponds to first 50 and 100 years of dam operation phase. يعد التنبؤ بتوزيع الرواسب في الخزانات مسألة مهمة لمصممي السدود لتحديد سعة التخزين الفعالة لبحيراتها، وعلى الرغم من تنوع الأساليب المقترحة لحساب توزيع الرواسب، التي هي في الغالب تجريبية، تعتبر طرائق تناقص وتزايد المساحة هي الطرائق الأساسية للتنبؤ بتوزيع الرواسب، من بين جميع الطرائق المتاحة حاليًا. تم في هذا البحث، دراسة توزيع الرواسب في بحيرة سد 16 تشرين في سورية، محافظة اللاذقية اعتمادا على الطرائق التجريبية (تزايد وتناقص المساحة). حيث استخدمنا البيانات الأولية عن المنسوب-مساحة والمنسوب -استطاعة تخزين للبحيرة والمعلومات التي تم الحصول عليها من خلال الهيدروغرافيا في السنوات التي تلت الاستثمار، عند إجراء العمليات الحسابية. اعتمادا على كلتا الطريقتين، تم حساب الترسيب في البحيرة ومقارنته بالقيم الفعلية التي تم الحصول عليها من المسح الهيدروغرافي في عام 2018. فأظهرت النتائج أن طريقة تناقص المساحة أفضل من طريقة تزايد المساحة بالنسبة لبحيرة سد 16-تشرين، إذ قللت الخطأ بنسبة 2 في المائة. بعد ذلك، تمت معايرة البارامترات المستخدمة في طريقة تناقص المساحة (c، m، n) فتحسنت نتائجها بحوالي 33 بالمائة. في النهاية وعلى أساس بارامترات المعايرة، تم التنبؤ عن الكيفية المتوقعة لتوزيع الرواسب في البحيرة خلال العشرين والسبعين سنة القادمة، أي بعد انقضاء 50 و100 سنة على دخول السد في الاستثمار.